Optical glass, optical elements and optical instruments

JP7645366B2Active Publication Date: 2025-03-13CDGM OPTICAL GLASS
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023519274
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-09-28
Filing Date
2021-07-28
Publication Date
2025-03-13
Estimated Expiration
2041-07-28

AI Technical Summary

Benefits of technology

【0023】 本発明の有益な効果は、以下の通りである。本発明により得られる光学ガラスは、所望の屈折率とアッべ数を有すると同時に、Pg,F値とΔPg,F値が比較的低く、化学的安定性に優れ、光透過率が高く、密度が比較的低い。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007645366000001
    Figure 0007645366000001
  • Figure 0007645366000002
    Figure 0007645366000002
  • Figure 0007645366000003
    Figure 0007645366000003
Patent Text Reader

Abstract

The present invention provides an optical glass containing the following components in weight percent: SiO2: 25-50%, ZrO2: 2-14%, Rn2O: 5-25%, Nb2O5: 25-50%, (Nb2O5+Rn2O) / SiO2 is 0.8-1.8, and Rn2O is one or more of Li2O, Na2O, and K2O. The optical glass obtained by the present invention has a desired refractive index and Abbe number, and also has a P g,F value and ΔP g,F It has relatively low values, excellent chemical stability, high light transmittance, and relatively low density.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an optical glass, and more particularly to an optical glass having a refractive index of 1.70-1.77 and an Abbe number of 28-36. [Background technology]

[0002] In recent years, with the development of micro (compact) high-definition optical systems, the refractive index is in the range of 1.70 to 1.77, the Abbe number is in the range of 28 to 36, and the P g,F value and ΔP g,F There is a strong demand for optical glass materials with a relatively low refractive index, a relatively low density, and a relatively high light transmittance. In the prior art, optical glasses with a refractive index within the above range mainly include lanthanum flint glass (LaF) and heavy flint glass (ZF). Summary of the Invention [Problem to be solved by the invention]

[0003] Lanthanum flint glass is P g,F Value and ΔP g,F The value is relatively low and can be used for secondary color difference correction, but lanthanum flint glass generally has a density of 4.0 g / cm 3 The acid resistance (D A ) is usually less than Class 3, or Class 4 or less. Lenses, prisms, etc. used in micro-optical systems are subject to the power and range of the drive motor, and have a density of 4.0 g / cm 3 If the temperature exceeds this limit, it will have a devastating effect on the entire design. In addition, unlike the processing of conventional optical components, the lenses and prisms used in micro-optical systems are processed in a strong acid and strong alkaline environment, and if the optical materials do not have excellent acid resistance, the yield rate of optical elements will drop significantly, and in some cases, products that pass the standards will not be obtained.

[0004] Conventional heavy flint glass within the above range of refractive index and Abbe number has low density, but has excellent chemical stability, and can meet the processing needs in a strong acid environment. However, conventional heavy flint glass has a low density, but has a low chemical stability, and can meet the processing needs in a strong acid environment.g,F The value is relatively large, which cannot meet the requirements of micro-optical systems to eliminate secondary color differences while reducing the lens assembly. Meanwhile, heavy flint glass generally has poor light transmittance, which cannot meet the high demand for light transmittance of micro-optical systems.

[0005] The technical problem that the present invention aims to solve is g,F Value and ΔP g,F The present invention aims to provide an optical glass having a relatively low refractive index, excellent chemical stability, high light transmittance, and a relatively low density. [Means for solving the problem]

[0006] The technical solutions adopted in the present invention to solve the technical problems are as follows. (1) Optical glass containing the following components by weight: SiO2: 25-50%, ZrO2: 2-14%, Rn2O: 5-25%, Nb2O5: 25-50%, (Nb2O5+Rn2O) / SiO2 is 0.8-1.8, and Rn2O is one or more of Li2O, Na2O, and K2O.

[0007] (2) The optical glass according to (1), further comprising the following components by weight: B2O3: 0-5%, and / or ZnO: 0-5%, and / or P2O5: 0-3%, and / or Al2O3: 0-5%, and / or MgO: 0-5%, and / or CaO: 0-8%, and / or SrO: 0-8%, and / or BaO: 0-8%, and / or La2O3: 0-5%, and / or Gd2O3: 0-5%, and / or Y2O3: 0-5%, and / or WO3: 0-5%, and / or Bi2O3: 0-5%, and / or TiO2: 0-5%, and / or a fining agent: 0-2%, and the fining agent is one or more of Sb2O3, SnO2, SnO, CeO2, NaCl, and sulfate.

[0008] (3) An optical glass containing, by weight percent, SiO2, Rn2O, and Nb2O5 as necessary components: (Nb2O5+Rn2O) / SiO2 is 0.8-1.8, the refractive index nd of the optical glass is 1.70-1.77, and the Abbe number νd 28~36, optical glass P g,F Value is 0.5950 or less, ΔP g,F value is 0.0015 or less, and Rn2O is one or more of Li2O, Na2O, and K2O.

[0009] (4) The optical glass according to (3), comprising, by weight, 25-50% SiO2, and / or 2-14% ZrO2, and / or 5-25% Rn2O, and / or 25-50% Nb2O5, and / or 0-5% B2O3, and / or 0-5% ZnO, and / or 0-3% P2O5, and / or 0-5% Al2O3, and / or 0-5% MgO, and / or 0-8% CaO, and / or 0-8% SrO, and / or B aO: 0-8%, and / or La2O3: 0-5%, and / or Gd2O3: 0-5%, and / or Y2O3: 0-5%, and / or WO3: 0-5%, and / or Bi2O3: 0-5%, and / or TiO2: 0-5%, and / or fining agent: 0-2%, Rn2O is one or more of Li2O, Na2O, and K2O, and the fining agent is one or more of Sb2O3, SnO2, SnO, CeO2, NaCl, and sulfate.

[0010] (5) Optical glass consisting of the following components by weight: SiO2: 25-50%, ZrO2: 2-14%, Rn2O: 5-25%, Nb2O5: 25-50%, B2O3: 0-5%, ZnO: 0-5%, P2O5: 0-3%, Al2O3: 0-5%, MgO: 0-5%, CaO: 0-8%, SrO: 0-8%, BaO: 0-8%, La2O3: 0-5%, Gd2O3 : 0-5%, Y2O3: 0-5%, WO3: 0-5%, Bi2O3: 0-5%, TiO2: 0-5%, fining agent: 0-2%, (Nb2O5+Rn2O) / SiO2 is 0.8-1.8, Rn2O is one or more of Li2O, Na2O, K2O, and the fining agent is one or more of Sb2O3, SnO2, SnO, CeO2, NaCl, and sulfate.

[0011] (6) An optical glass according to any one of (1) to (5), comprising the following components in weight percent and satisfying one or more of the following six conditions: 1) (Nb2O5+Rn2O) / SiO2 is 0.9~1.6; 2) Rn2O / SiO2 is 0.2-0.6; 3) Li2O / (Na2O+K2O) is 0.1-0.6; 4) K2O / Na2O is 0.1-0.7; 5) ZnO / ZrO2 is 0.01~1.5; 6) ZnO / RO is 10.0 or less. Rn2O is one or more of Li2O, Na2O, and K2O, and RO is the total content of BaO, SrO, CaO, and MgO.

[0012] (7) An optical glass according to any one of (1) to (5), comprising the following components by weight: SiO2: 28-47%, and / or ZrO2: 3-12%, and / or Rn2O: 6-23%, and / or Nb2O5: 28-45%, and / or B2O3: 0-3%, and / or ZnO: 0-4%, and / or P2O5: 0-1%, and / or Al2O3: 0-3%, and / or MgO: 0-3%, and / or CaO: 0-6%, and / or SrO: 0-5%. , and / or BaO: 0-6%, and / or La2O3: 0-3%, and / or Gd2O3: 0-3%, and / or Y2O3: 0-3%, and / or WO3: 0-3%, and / or Bi2O3: 0-3%, and / or TiO2: 0-3%, and / or fining agent: 0-1%, Rn2O is one or more of Li2O, Na2O, and K2O, and the fining agent is one or more of Sb2O3, SnO2, SnO, CeO2, NaCl, and sulfate.

[0013] (8) An optical glass according to any one of (1) to (5), comprising the following components in weight percent and satisfying one or more of the following six conditions: 1) (Nb2O5+Rn2O) / SiO2 is 1.0~1.5; 2) Rn2O / SiO2 is 0.23~0.55; 3) Li2O / (Na2O+K2O) is 0.2~0.5; 4) K2O / Na2O is 0.15~0.6; 5) ZnO / ZrO2 is 0.05~1.0; 6) ZnO / RO is 5.0 or less. Rn2O is one or more of Li2O, Na2O, and K2O, and RO is the total content of BaO, SrO, CaO, and MgO.

[0014] (9) An optical glass according to any one of (1) to (5), comprising the following components by weight: SiO2: 30-45%, and / or ZrO2: 5-10%, and / or Rn2O: 8-20%, and / or Nb2O5: 32-40%, and / or ZnO: 0-3%, and / or CaO: 0-5%, and / or SrO: 0-4%, and / or BaO: 0-5%, and / or La2O3: 0-2%, and / or Gd2O3: 0-2%, and / or Y2O3: 0-2%, and / or a fining agent: 0-0.5%, wherein Rn2O is one or more of Li2O, Na2O, and K2O, and the fining agent is one or more of Sb2O3, SnO2, SnO, CeO2, NaCl, and a sulfate.

[0015] (10) An optical glass according to any one of (1) to (5), comprising the following components in weight percent and satisfying one or more of the following five conditions: 1) Rn2O / SiO2 is 0.25~0.5; 2) Li2O / (Na2O+K2O) is 0.25~0.45; 3) K2O / Na2O is 0.2-0.5; 4) ZnO / ZrO2 is 0.1-0.5; 5) ZnO / RO is 3.0 or less, preferably ZnO / RO is 1.0 or less. Rn2O is one or more of Li2O, Na2O, and K2O, and RO is the total content of BaO, SrO, CaO, and MgO.

[0016] (11) The optical glass according to any one of (1) to (5), comprising, by weight, the following components: Li2O: 1 to 10%, preferably Li2O: 1.5 to 8%, more preferably Li2O: 2 to 6%, and / or Na2O: 2 to 20%, preferably Na2O: 4 to 18%, more preferably Na2O: 5 to 15%, and / or K2O: 0 to 8%, preferably K2O: 0 to 6%, more preferably K2O: 0.5 to 5%.

[0017] (12) An optical glass according to any one of (1) to (5) containing the following components by weight: SiO2+Nb2O5+ZrO2+Rn2O is 80% or more, preferably SiO2+Nb2O5+ZrO2+Rn2O is 85% or more, more preferably SiO2+Nb2O5+ZrO2+Rn2O is 88% or more, and even more preferably SiO2+Nb2O5+ZrO2+Rn2O is 91% or more.

[0018] (13) The optical glass according to any one of (1) to (5), which does not contain B2O3, and / or does not contain P2O5, and / or does not contain Al2O3, and / or does not contain MgO, and / or does not contain TiO2, and / or does not contain WO3, and / or does not contain Bi2O3, as its components.

[0019] (14) The refractive index n of the optical glass d is 1.70 to 1.77, preferably 1.705 to 1.765, more preferably 1.71 to 1.76, and further preferably 1.72 to 1.75; Abbe number ν d The optical glass according to any one of (1) to (5), wherein the refractive index is 28 to 36, preferably 29 to 35, more preferably 30 to 34, and further preferably 31 to 33.5.

[0020] (15) P of the optical glass g,F value is 0.5950 or less, preferably 0.5940 or less, more preferably 0.5930 or less, and / or ΔP g,F value is 0.0015 or less, preferably 0.0010 or less, more preferably 0.0005 or less, and even more preferably 0 or less, and / or acid resistance stability D AClass 2 or more, preferably Class 1, and / or water resistance D W is 2 or more, preferably 1, and / or light transmittance τ 400nm is 85.0% or more, preferably 88.0% or more, more preferably 90.0% or more, and / or density ρ is 3.80 g / cm 3 Less than 3.60 g / cm 3 Less than or equal to 3.40 g / cm 3 The optical glass according to any one of (1) to (5) below:

[0021] (16) The thermal expansion coefficient α of the optical glass 20 / 300℃ is 100 x 10 -7 / K or less, preferably 95×10 -7 / K or less, preferably 93×10 -7 The optical glass according to any one of (1) to (5), having a viscosity of 100 / K or less, and / or a weather resistance CR of Class 2 or higher, preferably Class 1, and / or a bubble content of Class A or higher, preferably A0 or higher, and / or a stripe content of Class D or higher, preferably Class C or higher, and / or an anti-crystallization property of Class B or higher, preferably Class A.

[0022] (17) A glass preform produced from the optical glass according to any one of (1) to (16). (18) An optical element produced from the optical glass according to any one of (1) to (16) or the glass preform according to (17). (19) An optical instrument comprising the optical glass according to any one of (1) to (16) and / or the optical element according to (18). Effect of the Invention

[0023] The beneficial effects of the present invention are as follows: The optical glass obtained by the present invention has a desired refractive index and Abbe number, and at the same time, P g,F Value and ΔP g,F It has relatively low values, excellent chemical stability, high light transmittance, and relatively low density. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] Hereinafter, the optical glass according to the present invention will be described in detail, but the present invention is not limited to the embodiments described below, and can be modified as appropriate within the scope of the object of the present invention. Furthermore, although some parts are omitted, the gist of the present invention is not limited by the repetition of the description. Hereinafter, the optical glass according to the present invention may be simply referred to as glass.

[0025] [Optical glass] The range of the components of the optical glass of the present invention will be described below. In this description, the content and total content of each component will be expressed in weight percent (wt%) unless otherwise specified. That is, the content and total content of each component will be expressed in weight percent relative to the total weight of the glass material converted into an oxide composition. "Converted into an oxide composition" here refers to the case where the total weight of the oxide material when the oxide, complex salt, hydroxide, etc. used as the raw material of the optical glass composition of the present invention is decomposed and converted into an oxide during melting is taken as 100%.

[0026] Specifically, the numerical ranges described herein include upper and lower limits, and the terms "greater than or equal to" and "less than or equal to" include the endpoints, and all integers and fractions subsumed within the range, but are not limited to the specific values ​​set forth when the range is limited. As used herein, "and / or" is inclusive, e.g., "A and / or B" means A only, B only, or both A and B.

[0027] <Required and optional ingredients> In the present invention, SiO2 is a network forming component, and if its content exceeds 50%, the refractive index of the glass is lower than the design requirement, the Abbe number is higher than the design requirement, and the melting performance of the glass is poor. If its content is less than 25%, the broken network bonds inside the glass rapidly increase, the chemical stability decreases, and the anti-crystallization property rapidly decreases. Therefore, the content of SiO2 is limited to 25-50%, preferably 28-47%, and more preferably 30-45%.

[0028] An appropriate amount of B2O3 can increase the Abbe number of the glass, lower the melting temperature of the glass, and reduce the probability of insoluble matter in the glass. However, in the glass system of the present invention, if the content of B2O3 exceeds 5%, the free oxygen in the glass will be lost, and some oxides whose valence has changed will transition to low valence, resulting in a rapid deterioration of the light transmittance. On the other hand, if the content of B2O3 exceeds 5%, the P of the glass will be reduced. g,F This will cause a rapid increase in the value, making it impossible to meet the design requirements. Therefore, the content of B2O3 is limited to 5% or less, preferably 3% or less, and more preferably no B2O3.

[0029] Although the Abbe number of glass can be adjusted by adding P2O5, in this type of glass, P2O5 exceeding 3% forms a large amount of crystal nuclei in the glass, and the crystallization resistance of the glass rapidly deteriorates. Therefore, the P2O5 content is limited to 3% or less, preferably 1% or less, and more preferably, no P2O5 is contained.

[0030] Although the use of Al2O3 in glass can improve the chemical stability of the glass, if its content exceeds 5%, the crystallization resistance of the glass will rapidly deteriorate and a large amount of stones will form inside the glass. Therefore, the content of Al2O3 is 5% or less, preferably 3% or less. In some embodiments, Al2O3 is P g,F Since it has the effect of increasing the value, it is more preferable that Al2O3 is not contained.

[0031] Nb2O5 is a high refractive index, high dispersion component, and one of the main components of the glass of the present invention. If the content of Nb2O5 is less than 25%, the P required for the glass of the present invention can be obtained. g,F value and ΔP g,F If the content exceeds 50%, the refractive index of the glass exceeds the designed value, and the crystallization resistance of the glass rapidly deteriorates. Therefore, the content of Nb2O5 is 25 to 50%, preferably 28 to 45%, and more preferably 32 to 40%.

[0032] Although TiO2 can increase the chemical stability of glass and reduce the thermal expansion coefficient of glass, if its content exceeds 5%, the light transmittance of glass will rapidly deteriorate, especially when components such as B2O3 and Al2O3 are present in the glass. Therefore, its content is limited to 5% or less, preferably 3% or less. In some embodiments, TiO2 can reduce the ΔP of glass. g,F Since the value can be rapidly increased, it is more preferable not to include TiO2.

[0033] The use of ZrO2 in glass can significantly improve the crystallinity of the glass, but the above effect is not significant, especially when the content of Nb2O5 exceeds 25%, and when the content of ZrO2 is less than 2%. When the content of ZrO2 exceeds 14%, the solubility of ZrO2 decreases rapidly, forming minute insoluble matters inside the glass, deteriorating the quality of the inside of the glass, and more seriously, these minute insoluble matters become crystallization carriers, significantly reducing the crystallinity of the glass. Therefore, the content of ZrO2 is 2-14%, preferably 3-12%, more preferably 5-10%.

[0034] The use of an appropriate amount of alkali metal oxide Rn2O (Rn2O is one or more of Li2O, Na2O, and K2O) in glass increases the solubility of Nb2O5, ZrO2, and other substances that are difficult to melt, and improves the refractive index, Abbe number, and P g,F Value and ΔP g,F The value can easily meet the design requirements, but when the content of Rn2O is less than 5%, the above effects are not significant. When the content of Rn2O exceeds 25%, the broken bonds in the glass structure increase rapidly, and the crystallization resistance of the glass also decreases rapidly. Therefore, the content of Rn2O is 5-25%, preferably 6-23%, more preferably 8-20%.

[0035] In some embodiments, in order to achieve the desired excellent glass performance, in particular to obtain a relatively low density and a relatively high light transmittance, it is preferable to control the total content of SiO2, Nb2O5, ZrO2, and Rn2O, SiO2+Nb2O5+ZrO2+Rn2O, to be 80% or more, more preferably SiO2+Nb2O5+ZrO2+Rn2O to be 85% or more, even more preferably SiO2+Nb2O5+ZrO2+Rn2O to be 88% or more, and even more preferably SiO2+Nb2O5+ZrO2+Rn2O to be 91% or more.

[0036] As a result of extensive experimental research conducted by the inventors, it has been found that in some embodiments, the value of (Nb2O5+Rn2O) / SiO2 is controlled within the range of 0.8 to 1.8, thereby reducing the P content of the glass. g,F Value and ΔP g,F It has been found that the value can easily reach the desired range and the stability of the glass can be improved. Therefore, (Nb2O5+Rn2O) / SiO2 is preferably 0.9 to 1.6, and more preferably 1.0 to 1.5.

[0037] As a micro-optical instrument, its imaging operating surface is much smaller than other imaging instruments, so the requirements for the quality of the glass interior are much higher than other imaging instruments, and even a small amount of bubbles, inclusions, or stripes in the glass will have a significant impact on the imaging quality of the micro-imaging instrument. Research has shown that if the bubble degree of the optical glass used in the micro-imaging instrument does not reach grade A0 or above and the stripe does not reach grade D or above, it cannot meet the optical grade imaging requirements of the micro-imaging instrument. The glass composition system used in the glass of the present invention has a relatively high viscosity in the optical glass system, which is unfavorable to the increase of the bubble degree and stripe. After a large amount of experimental research, the inventors found that if the value of Rn2O / SiO2 is 0.2 or more, the high-temperature viscosity of the glass can be improved, a high bubble degree and stripe grade of the glass can be achieved, and the quality of the glass interior can be improved, but if the value of Rn2O / SiO2 exceeds 0.6, the thermal expansion coefficient of the glass will increase, causing fatal damage to the manufacture of micro-imaging instruments that need to be bonded under high-temperature conditions. Therefore, in the present invention, the value of Rn2O / SiO2 is preferably from 0.2 to 0.6, more preferably from 0.23 to 0.55, and further preferably from 0.25 to 0.5.

[0038] Among the three alkali metal oxides, Li2O, Na2O, and K2O, Li2O has the strongest ability to increase the solubility of raw materials, but because the electric field strength is relatively large, if the content of Li2O exceeds 10%, it will promote the deterioration of the crystallinity resistance of the glass. If the content of Li2O is less than 1%, the contents of Na2O and K2O must be increased to maintain the solubility of the substances that are difficult to melt, but this will cause a rapid deterioration of the chemical stability of the glass. Therefore, the content of Li2O is 1 to 10%, preferably 1.5 to 8%, and more preferably 2 to 6%.

[0039] If the Na2O content exceeds 20%, the chemical stability of the glass will not meet the design requirements, and if the content is less than 2%, the glass will be difficult to melt. Therefore, the Na2O content is limited to 2-20%, preferably 4-18%, and more preferably 5-15%.

[0040] The use of K2O in glass rapidly reduces the chemical stability of the glass, and potassium is most likely to precipitate, especially in strong acid and strong alkaline environments. Therefore, the content of K2O is limited to 8% or less, preferably 6% or less. In some embodiments, the three alkali metal oxides Li2O, Na2O, and K2O have a synergistic effect to optimize the performance of the glass, so the content of K2O is more preferably 0.5-5%.

[0041] As a result of extensive experimental research, the inventors have found that Li2O, Na2O, and K2O have a complex synergistic effect in glass, and the content ratio of these elements has a significant effect on important indexes such as the crystallization resistance, light transmittance, chemical stability, and thermal expansion coefficient of glass.

[0042] Li2O has a strong ability to increase the solubility of difficult-to-melt substances and can reduce the thermal expansion coefficient of glass, but because of its large electric field strength, when added alone to glass, it tends to promote crystal precipitation in glass. In some embodiments, when Na2O and K2O are present in glass, the ability of Li2O to promote crystal precipitation is reduced, and in particular when Li2O / (Na2O+K2O) is 0.1 to 0.6, preferably 0.2 to 0.5, and more preferably 0.25 to 0.45, the glass has excellent crystallinity resistance and the thermal expansion coefficient of glass does not exceed the design requirement.

[0043] Na2O and K2O can increase the solubility of difficult-to-melt substances, improve the stability of glass, and optimize the light transmittance of glass, but they rapidly reduce the chemical stability of glass, especially when Na2O or K2O is contained alone. As a result of extensive experimental research, the inventors have found that in some embodiments, when Na2O and K2O are both present in glass and the content of K2O and Na2O satisfies the range of K2O / Na2O of 0.1 to 0.7, the glass has high solubility and light transmittance, and is also excellent in chemical stability. Preferably, K2O / Na2O is 0.15 to 0.6, and more preferably, K2O / Na2O is 0.2 to 0.5.

[0044] ZnO can increase the refractive index and dispersion of glass, reduce the high-temperature viscosity of glass, and increase the degree of bubbles and stripes of glass. If its content exceeds 5%, the tendency of phase separation of glass increases, the stripes are greatly reduced, and the P of glass g,F Value and ΔP g,F Therefore, the ZnO content is limited to 5% or less, preferably 4% or less, and more preferably 3% or less.

[0045] As a result of extensive experimental research, the inventors have found that in some embodiments, a small amount of ZnO can significantly improve the solubility of ZrO2 in glass, and that the effect of improving the solubility of ZrO2 in glass is particularly excellent when the ZnO / ZrO2 value is 0.01 to 1.5, preferably 0.05 to 1.0, and more preferably 0.1 to 0.5.

[0046] BaO can adjust the dispersion of glass, but if its content exceeds 8%, the chemical performance of glass will be deteriorated and the ΔP of glass will be g,F Therefore, the BaO content is 8% or less, preferably 6% or less, and more preferably 5% or less.

[0047] CaO can adjust the dispersion of glass, and the effect of increasing the Abbe number of glass by CaO is superior to that of BaO. However, if the CaO content exceeds 8%, the crystallization resistance of glass decreases, and the ΔP g,F Therefore, the CaO content is limited to 8% or less, preferably 6% or less, and more preferably 5% or less.

[0048] SrO can increase the stability of glass, improve the crystallization resistance of glass, and increase the Abbe number of glass. However, when its content exceeds 8%, the Abbe number of glass is higher than the design requirement, and the ΔP of glass is g,F Therefore, the content of SrO is limited to 8% or less, preferably 5% or less, and more preferably 4% or less.

[0049] Although MgO can increase the chemical stability of glass, if its content exceeds 5%, the crystallization resistance of glass will rapidly decrease. Therefore, the content of MgO is limited to 5% or less, preferably 3% or less, and more preferably, no MgO is contained.

[0050] As a result of extensive experimental research, the inventors have found that in some embodiments, the ratio of the content of ZnO to the content of alkaline earth metal oxides RO (RO is the total content of BaO, SrO, CaO, and MgO) has a significant effect on the crystallinity resistance of optical glass. Specifically, when the value of ZnO / RO exceeds 10.0, the crystallinity resistance of the glass rapidly deteriorates. Therefore, the value of ZnO / RO is preferably 10.0 or less, more preferably 5.0 or less, even more preferably 3.0 or less, and even more preferably 1.0 or less.

[0051] La2O3 can increase the refractive index of glass, reduce the high-temperature viscosity of glass, and improve the internal quality of glass. However, when its content exceeds 5%, the crystallization resistance of glass deteriorates, the Abbe number increases rapidly, and the ΔP g,F Therefore, the La2O3 content is limited to 5% or less, preferably 3% or less, and more preferably 2% or less.

[0052] Y2O3 can increase the refractive index and dispersion of glass, strengthen the network cohesion of glass, and improve the chemical stability of glass. When the content of Y2O3 exceeds 5%, the glass network will be excessively cohesed, the crystallization resistance of glass will rapidly decrease, and the density will rapidly increase. Therefore, the content of Y2O3 is limited to 5% or less, preferably 3% or less, and more preferably 2% or less.

[0053] Gd2O3 can increase the refractive index and dispersion of glass and improve the stability of glass, but if its content exceeds 5%, stones are likely to form inside the glass, and the internal quality will not meet the design requirements. Therefore, the content of Gd2O3 is limited to 5% or less, preferably 3% or less, and more preferably 2% or less.

[0054] WO3 increases the dispersion of glass, decreases the Abbe number of glass, and increases ΔP g,F The value can easily meet the design requirements, but if its content exceeds 5%, the crystallinity resistance and light transmittance of the glass will rapidly decrease. Therefore, the content of WO3 is limited to 5% or less, preferably 3% or less, and more preferably does not contain WO3.

[0055] Bi2O3 increases the dispersibility of the glass, decreases the Abbe number of the glass, and increases the ΔP g,F The value can easily meet the design requirements, but when its content exceeds 5%, the light transmittance of the glass drops rapidly and the density rises rapidly. Therefore, the content of Bi2O3 is limited to 5% or less, preferably 3% or less. In some embodiments, the glass of the present invention needs to be produced in a platinum container, but since Bi2O3 has a strong corrosive effect on the platinum container, it is more preferable to not contain Bi2O3.

[0056] The glass of the present invention may contain a small amount of fining agent such as Sb2O3, SnO2, SnO, CeO2, NaCl, sulfate, etc., to improve the bubble content of the glass, and the content of the fining agent is limited to 0-2%, preferably 0-1%, more preferably 0-0.5%. In consideration of the existing production technology, it is preferable to use Sb2O3 as the fining agent.

[0057] <Ingredients that should not be included> In the glass of the present invention, even when oxides of transition metals such as V, Cr, Mn, Fe, Co, Ni, Cu, Ag, and Mo are contained alone or in combination in small amounts, the glass is colored and specific wavelengths in the visible light region are absorbed, weakening the visible light transmission effect of the present invention. Therefore, it is preferable that optical glasses which require wavelength transmittance in the visible light region in particular not actually contain such oxides.

[0058] In recent years, there has been a trend to restrict the use of oxides of Th, Cd, Tl, Os, Be and Se as harmful chemicals, and environmental protection efforts are required not only in the glass manufacturing process, but also in the processing process and disposal of the finished product. Therefore, when the impact on the environment is important, it is preferable that they are not included except for unavoidable contamination. This makes the optical glass actually free of substances that pollute the environment. Therefore, the optical glass of the present invention can be manufactured, processed and disposed of without taking special environmental measures.

[0059] In consideration of the environment, the optical glass of the present invention does not contain As2O3 and PbO. As2O3 has the effect of removing bubbles and preventing coloring of the glass, but the addition of As2O3 increases the platinum erosion in the glass melting furnace, especially the platinum melting furnace, so that more platinum ions enter the glass, which adversely affects the service life of the platinum melting furnace. PbO can significantly increase the high refractive index and high dispersion of the glass, but both PbO and As2O3 are substances that cause environmental pollution.

[0060] The terms "free" and "0%" used in this specification mean that no compounds, molecules, ions, elements, etc. were intentionally added as raw materials for the optical glass of the present invention. However, as raw materials and / or equipment for manufacturing the optical glass, impurities or components that are not intentionally added may exist in small or trace amounts in the final optical glass, and these are also covered by the patent of the present invention.

[0061] The characteristics of the optical glass of the present invention will be described below. <Refractive index and Abbe number> The refractive index of optical glass (n d ) and Abbe number (ν d ) is tested in accordance with the method specified in "GB / T 7962.1-2010". In some embodiments, the refractive index (n d ) has an upper limit of 1.77, preferably an upper limit of 1.765, more preferably an upper limit of 1.76, and even more preferably an upper limit of 1.75. In some embodiments, the refractive index (n d ) has a lower limit of 1.70, preferably a lower limit of 1.705, more preferably a lower limit of 1.71, and even more preferably a lower limit of 1.72. In some embodiments, the Abbe number (ν d ) is 36, preferably 35, more preferably 34, and even more preferably 33.5. In some embodiments, the Abbe number (ν d ) has a lower limit of 28, preferably a lower limit of 29, more preferably a lower limit of 30, and even more preferably a lower limit of 31.

[0062] <P g,F Value and ΔP g,F Value> Optical glass P g,F Value and ΔP g,F is the n of glass according to the method specified in "GB / T 7962.1-2010". F , n C , n g The value is measured and calculated according to the following formula: P g,F = (n g -n F ) / (n F -n C ) ΔP g,F = P g,F -0.6457 + 0.001703ν d In some embodiments, the P of the optical glass of the present invention g,F The value is 0.5950 or less, preferably 0.5940 or less, and more preferably 0.5930 or less. In some embodiments, the ΔP of the optical glass of the present invention g,F The value is 0.0015 or less, preferably 0.0010 or less, more preferably 0.0005 or less, and even more preferably 0 or less.

[0063] <Thermal expansion coefficient> Thermal expansion coefficient of optical glass (α 20 / 300℃) measures the data of optical glass at temperatures between 20℃ and 300℃ according to the method specified in "GB / T 7962.16-2010". In some embodiments, the thermal expansion coefficient (α 20 / 300℃ ) is 100 x 10 -7 / K or less, preferably 95×10 -7 / K or less, preferably 93×10 -7 / K or less.

[0064] <Water resistance stability> Water resistance stability of optical glass (D W ) (powder method) is tested according to the method specified in "GB / T 17129". In some embodiments, the water resistance stability (D W ) is class 2 or more, preferably class 1.

[0065] <Acid resistance stability> Acid resistance stability of optical glass (D A ) (powder method) is tested according to the method specified in "GB / T 17129". In some embodiments, the acid resistance stability (D A ) is class 2 or more, preferably class 1.

[0066] <density> The density (ρ) of optical glass is tested according to the method specified in "GB / T7962.20-2010". In some embodiments, the density (ρ) of the optical glass of the present invention is 3.80 g / cm 3 Less than 3.60 g / cm 3 Less than or equal to 3.40 g / cm 3 The following is the result.

[0067] <Anti-crystalline> The crystallinity of the glasses of the present invention is tested according to the following method. The sample is processed into 20×20×10mm, polished on both sides, put the sample into a crystallization furnace at a temperature of Tg+200℃ and kept warm for 30 minutes, then taken out and cooled, and polished again on the two large surfaces. The crystallinity of the glass is judged according to the following Table 1, with grade A being the best and grade E being the worst.

[0068] [Table 1]

[0069] In some embodiments, the optical glass of the present invention has a crystallization resistance of Class B or higher, preferably Class A, and is excellent in crystallization resistance.

[0070] <Stripe> The stripes of the glass of the present invention are tested according to the method specified in "MLL-G-174B". Using a stripe meter consisting of a point light source and a lens, a standard sample is compared and confirmed from the direction where the stripes are most visible. There are four grades, A, B, C, and D. Grade A means that no visible stripes are visible under the specified detection conditions, grade B means that fine scattered stripes are visible under the specified detection conditions, grade C means that faint parallel stripes are visible under the specified detection conditions, and grade D means that coarse stripes are visible under the specified detection conditions. In some embodiments, the stripes of optical glass are Class D or better, preferably Class C or better.

[0071] <Light transmittance> Optical glass light transmittance (τ 400nm ) is tested in accordance with the method specified in "GB / T 7962.12-2010". In some embodiments, the optical transmittance (τ 400nm ) is 85.0% or more, preferably 88.0% or more, and more preferably 90.0% or more.

[0072] <Bubble level> The bubble content of optical glass is tested according to the method specified in "GB / T7962.8-2010". In some embodiments, the bubble content of the optical glass of the present invention is Class A or higher, preferably Class A0 or higher.

[0073] <Weather resistance> The weatherability (CR) of optical glass is tested according to the following method. The sample is placed in a test box with a saturated water vapor environment of 90% relative humidity, and alternately circulated at 40-50℃ every hour, 15 times. The weather resistance is classified according to the amount of change in turbidity before and after leaving the sample. Table 2 shows the weather resistance classification conditions.

[0074] [Table 2]

[0075] In some embodiments, the weather resistance (CR) of the optical glass of the present invention is Class 2 or higher, and preferably Class 1.

[0076] [Method of manufacturing optical glass] The method for producing the optical glass of the present invention is as follows. The glass of the present invention is produced by conventional raw materials and processes using carbonates, nitrates, sulfates, phosphates, metaphosphates, hydroxides, oxides, etc. as raw materials, and after mixing by a conventional method, the prepared furnace material is put into a melting furnace (platinum crucible, quartz crucible, etc.) at 1300 to 1350 ° C. and melted. Then, it is clarified, stirred, and homogenized to obtain a homogeneous molten glass without bubbles or unmelted materials, and this molten glass is cast into a mold and annealed. Those skilled in the art can appropriately select raw materials, manufacturing methods, and process parameters according to actual needs.

[0077] [Glass preforms and optical elements] A glass preform can be produced from the produced optical glass using press molding means such as polishing, hot press molding, precision press molding, etc. That is, an optical preform can be produced from the optical glass by mechanical processing such as grinding and polishing, or a blank for press molding can be produced from the optical glass, and this blank can be hot press molded and then polished to produce an optical preform, or the blank produced by polishing can be precision press molded to produce an optical preform. It should be noted that the means for producing the optical preform are not limited to the above means.

[0078] As described above, the optical glass of the present invention is useful for various optical elements and optical designs, and it is particularly preferable to form a blank from the optical glass of the present invention and use this blank to carry out hot press molding, precision press molding, etc. to produce optical elements such as lenses, prisms, etc. The glass of the present invention can also be used to manufacture glass preforms using a primary droplet molding method.

[0079] The optical preform and optical element of the present invention are both formed from the optical glass of the present invention. The optical preform of the present invention has the excellent properties of optical glass, and the optical element of the present invention has the excellent properties of optical glass, making it possible to provide optical elements such as various lenses and prisms with high optical value. Examples of lenses include various lenses, such as a concave meniscus lens, a convex meniscus lens, a biconvex lens, a biconcave lens, a plano-convex lens, and a plano-concave lens, each of which has a spherical or aspheric lens surface.

[0080] [Optical equipment] The optical glass or optical element formed from the optical glass of the present invention can be used in the manufacture of optical equipment such as photography devices, imaging devices, display devices, and monitor devices. The optical glass or optical element of the present invention is suitable for use in vehicle-mounted lighting equipment and optical equipment, and is applied to fields such as vehicle-mounted equipment. The optical glass or optical element of the present invention is suitable for use in optical equipment such as microprojection, microimaging (imaging / photography), and microillumination. EXAMPLES

[0081] <Examples of optical glass> In order to further clearly illustrate the technical solutions of the present invention, the following non-limiting examples are provided. In the present examples, the optical glass was obtained using the above-mentioned optical glass manufacturing method, and has the composition shown in Tables 3 and 4. The properties of each glass were measured by the test methods described in the present invention, and the results are shown in Tables 3 and 4.

[0082] [Table 3]

[0083] [Table 4]

[0084] <Example of glass preform> The glasses obtained in Examples 1 to 15 of the optical glass are subjected to polishing, hot press molding, precision press molding, or other press molding means to produce various lenses, such as concave meniscus lenses, convex meniscus lenses, biconvex lenses, biconcave lenses, plano-convex lenses, and plano-concave lenses, as well as preforms such as prisms.

[0085] <Examples of optical elements> These preforms obtained in the above glass preform examples can be unannealed or annealed, provided that the stress is guaranteed, i.e. the refractive index can be fine-tuned while reducing the stress inside the glass, so that the optical properties such as the refractive index reach the desired values. Each preform is then ground and polished to produce various lenses and prisms, such as concave meniscus lenses, convex meniscus lenses, biconvex lenses, biconcave lenses, plano-convex lenses, and plano-concave lenses. An anti-reflective coating can also be applied to the surfaces of the obtained optical elements.

[0086] <Examples of optical equipment> The optical elements manufactured according to the above optical element embodiments can be used in imaging devices, sensors, microscopes, medical technology, digital projection, communication, optical communication technology / information transmission, optics / illumination in the automotive field, photolithography technology, excimer lasers, wafers, computer chips and integrated circuits and electronic devices containing such circuits and chips, or imaging equipment and devices in the automotive field by forming optical parts or components using one or more optical elements according to optical design.

Claims

1. An optical glass containing the following components by weight and satisfying the following conditions: SiO 2 : 25-50%, ZrO 2 : 2-14%, Rn 2 O: 5-25%, and Nb 2 O 5 : 25-50%. (Nb 2 O 5 +Rn 2 O) / SiO 2 (weight ratio) is 0.8 to 1.8, Li 2 O / (Na 2 O+K 2 O) (weight ratio) is 0.2 to 0.6, ZnO / ZrO 2 (weight ratio) is 0.01 to 1.5, K 2 O / Na 2 O (weight ratio) is 0.1 to 0.7, and the total content of SiO 2 , Nb 2 O 5 , ZrO 2 , and Rn 2 O is 91% or more. Here, Rn 2 O is Li 2 O, Na 2 O and K 2 O.

2. 2. The optical glass according to claim 1, further comprising one or more components selected from the following group by weight percent: B 2 O 3 : 0-5%, ZnO: 0-5%, P 2 O 5 : 0-3%, Al 2 O 3 : 0~5%, MgO: 0~5%, CaO: 0~8%, SrO: 0~8%, BaO: 0~8%, La 2 O 3 : 0-5%, Gd 2 O 3 : 0-5%, Y 2 O 3 : 0-5%, WO 3 : 0-5%, Bi 2 O 3 : 0-5%, TiO 2 : 0-5%, and clarifier: 0-2%. Here, the fining agent is Sb 2 O 3 , SnO 2 , SnO, CeO 2 , NaCl, and sulfates.

3. SiO as a necessary component 2 , Rn 2 O and Nb 2 O 5 and satisfying the following conditions: (Nb 2 O 5 +Rn 2 O) / SiO 2 (weight ratio) is 0.8 to 1.8, Li 2 O / (Na 2 O+K 2 O) (weight ratio) is 0.2 to 0.6, ZnO / ZrO 2 (weight ratio) is 0.01 to 1.5, K 2 O / Na 2 O (weight ratio) is 0.1 to 0.7, the total content of SiO 2 , Nb 2 O 5 , ZrO 2 and Rn 2 O is 91% or more, and the refractive index n d is 1.70 to 1.77, Abbe number ν d 28-36, optical glass P g,F Value is 0.5950 or less, ΔP g,F The value is less than or equal to 0.0015. Here, Rn 2 O is Li 2 O, Na 2 O and K 2 O.

4. 4. The optical glass according to claim 3, comprising one or more components selected from the following group by weight percent: SiO 2 : 25-50%, ZrO 2 : 2-14%, Rn 2 O: 5-25%, Nb 2 O 5 : 25-50%, B 2 O 3 : 0-5%, ZnO: 0-5%, P 2 O 5 : 0-3%, Al 2 O 3 : 0~5%, MgO: 0~5%, CaO: 0~8%, SrO: 0~8%, BaO: 0~8%, La 2 O 3 : 0-5%, Gd 2 O 3 : 0-5%, Y 2 O 3 : 0-5%, WO 3 : 0-5%, Bi 2 O 3 : 0-5%, TiO 2 : 0-5%, and clarifier: 0-2%. Here, Rn 2 O is Li 2 O, Na 2 O and K 2 O, and the fining agent is Sb 2 O 3 , SnO 2 , SnO, CeO 2 , NaCl, and sulfates.

5. 5. The optical glass according to claim 1, which satisfies one or more of the following three conditions: 1)(Nb 2 O 5 +Rn 2 O) / SiO 2 (weight ratio) is 0.9-1.6; 2) Rn 2 O / SiO 2 (weight ratio) is 0.2-0.6; 3) ZnO / RO (weight ratio) is 10.0 or less. Here, Rn 2 O is Li 2 O, Na 2 O and K 2 O is one or more selected from the group consisting of BaO, SrO, CaO, and MgO.

6. 5. The optical glass according to claim 1, comprising one or more components selected from the following group by weight percent: SiO 2 : 28-47%, ZrO 2 : 3-12%, Rn 2 O: 6-23%, Nb 2 O 5 : 28-45%, B 2 O 3 : 0-3%, ZnO: 0-4%, P 2 O 5 : 0-1%, Al 2 O 3 : 0~3%, MgO: 0~3%, CaO: 0~6%, SrO: 0~5%, BaO: 0~6%, La 2 O 3 : 0-3%, Gd 2 O 3 : 0-3%, Y 2 O 3 : 0-3%, WO 3 : 0-3%, Bi 2 O 3 : 0-3%, TiO 2 : 0-3%, and clarifier: 0-1%. Here, Rn 2 O is Li 2 O, Na 2 O and K 2 O, and the fining agent is Sb 2 O 3 , SnO 2 , SnO, CeO 2 , NaCl, and sulfates.

7. An optical glass according to any one of claims 1 to 4, which satisfies one or more of the following six conditions: 1)(Nb 2 O 5 +Rn 2 O) / SiO 2 (weight ratio) is 1.0-1.5; 2) Rn 2 O / SiO 2 (weight ratio) is 0.23-0.55; 3) Li 2 O / (Na 2 O+K 2 O) (weight ratio) is 0.2 to 0.5; 4) K 2 O / Na 2 O (weight ratio) is 0.15-0.6; 5) ZnO / ZrO 2 (weight ratio) is 0.05 to 1.0; 6) ZnO / RO (weight ratio) is 5.0 or less. Here, Rn 2 O is Li 2 O, Na 2 O and K 2 O is one or more selected from the group consisting of BaO, SrO, CaO, and MgO.

8. 5. The optical glass according to claim 1, comprising one or more components selected from the following group by weight percent: SiO 2 : 30-45%, ZrO 2 : 5-10%, Rn 2 O: 8-20%, Nb 2 O 5 :32~40%, ZnO: 0~3%, CaO: 0~5%, SrO: 0~4%, BaO: 0~5%, La 2 O 3 : 0-2%, Gd 2 O 3 : 0-2%, Y 2 O 3 : 0-2%, and fining agent: 0-0.5%, where Rn 2 O is Li 2 O, Na 2 O and K 2 O, and the fining agent is Sb 2 O 3 , SnO 2 , SnO, CeO 2 , NaCl, and sulfates.

9. An optical glass according to any one of claims 1 to 4, which satisfies one or more of the following five conditions: 1) Rn 2 O / SiO 2 (weight ratio) is 0.25-0.5; 2) Li 2 O / (Na 2 O+K 2 O) (weight ratio) is 0.25 to 0.45; 3) K 2 O / Na 2 O (weight ratio) is 0.2-0.5; 4) ZnO / ZrO 2 (weight ratio) is 0.1-0.5; 5) ZnO / RO (weight ratio) is 3.0 or less. Here, Rn 2 O is Li 2 O, Na 2 O and K 2 O is one or more selected from the group consisting of BaO, SrO, CaO, and MgO.

10. 5. The optical glass according to claim 1, comprising one or more components selected from the following group by weight percent: Li 2 O: 1-10%, Na 2 O: 2-20%, and K 2 O: Group consisting of 0-8%.

11. 5. The optical glass according to claim 1, comprising one or more components selected from the following group by weight percent: Li 2 O: 2-6%, Na 2 O: 5-15% and K 2 O: 0.5-5% group.

12. B 2 O 3 , P 2 O 5 , Al 2 O 3 , MgO, TiO 2 , WO 3 , and Bi 2 O 3 5. The optical glass according to claim 1, which does not contain one or more components selected from the group consisting of:

13. The refractive index n of the optical glass d is 1.70 to 1.77, Abbe number ν d The optical glass according to any one of claims 1 to 4, wherein the refractive index is 28 to 36.

14. The refractive index n of the optical glass d is 1.71 to 1.76, Abbe number ν d The optical glass according to any one of claims 1 to 4, wherein the refractive index is 30 to 34.

15. The optical glass according to any one of claims 1 to 4, which satisfies one or more of the following eleven conditions: 1) P of the optical glass g,F The value is less than or equal to 0.5950. 2) ΔP g,F The value is less than or equal to 0.0015. 3) Acid resistance stability D A is Class 2 or higher. 4)Water resistance stability D W is Class 2 or higher. 5) Light transmittance τ 400nm is 85.0% or more. 6) Density ρ is 3.80 g / cm 3 The following is the result. 7) Thermal expansion coefficient α 20 / 300℃ is 100 x 10 -7 / K or less. 8) Weather resistance CR is Class 2 or higher. 9) The degree of foaming is A grade or higher. 10) The stripes are D grade or higher. 11) The crystallization resistance is class B or higher.

16. The optical glass according to any one of claims 1 to 4, which satisfies one or more of the following eleven conditions: 1) P of the optical glass g,F The value is less than or equal to 0.5930. 2) ΔP g,F The value is less than or equal to 0. 3) Acid resistance stability D A is Class 1. 4)Water resistance stability D W is Class 1. 5) Light transmittance τ 400nm is 90.0% or more. 6) Density ρ is 3.40 g / cm 3 The following is the result. 7) Thermal expansion coefficient α 20 / 300℃ is 93×10 -7 / K or less. 8) Weather resistance CR is Class 1. 9) Bubble level: A 0 Grade or above. 10) The stripes are C grade or higher. 11) The crystallization resistance is Class A.

17. A glass preform made of the optical glass according to any one of claims 1 to 16.

18. An optical element produced from the optical glass according to any one of claims 1 to 16 or the glass preform according to claim 17.

19. An optical instrument comprising the optical glass according to any one of claims 1 to 16 and / or the optical element according to claim 18.

Citation Information

Patent Citations

  • Optical glass

    JP2007169157A

  • Optical glass and optical element

    JP2017007933A

  • Optical glass, preform and optical element

    JP2017105702A

  • Optical glass, preform and optical element

    JP2017105703A

  • Optical glass, preform and optical element

    JP2019064876A